PERUBAHAN MOTIF WISATA RELIGI KALANGAN GENERASI Z DI MAKAM NYAI HAMDANAH KUDUS - Maghfirotunnisa, Maghfirotunnisa; Savitri, Fania Mutiara (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2025)
The Tomb of Nyai Hamdanah Kudus is one of the popular tourist destinations on social media because it is believed to be a testament to be a means of finding a pious soul mate. Viral content about the blessings of the tomb attracts many pilgrims, especially generation Z to come on a pilgrimage. If previously pilgrimages focused more on spiritual aspects and remembering death, now Generation Z does it with various purposes, for example: seeking the blessing of a soul mate, following social media trends, or simply creating content. This shows that there is a change in pilgrimage motifs among generation Z, especially at the Tomb of Nyai Hamdanah Kudus. The purpose of this study is to identify changes in pilgrimage motifs among generation Z at the Tomb of Nyai Hamdanah Kudus and analyze the factors that influence change in the motives for pilgrimage at the tomb. The research method used in this study is a qualitative method using a case study approach through interviews, observation and documentation in data collection, as well as using data analysis techniques which include data reduction, data presentation, and conclusion drawn. The results of the study show that pilgrimage activities at the Nyai Hamdanah’s Tomb has changed its motives among generation Z. Initially, pilgrimages was carried out for religious purposes such as tawasul and tabarukan. However, among Generation Z, these motives have developed into more diverse including asking for a soul mate, seeking inner peace, to following trends on social media driven by FOMO. The change in motives is influenced by three main factors, namely: social, religiosity, and psychological. This phenomenon shows that the motive of pilgrimage is now not only spiritual, but also related to the social and psychological influence that develops in society.